Arrdc4‐dependent extracellular vesicle biogenesis is required for sperm maturation. Issue 8 (22nd June 2021) - Foot, Natalie J.; Gonzalez, Macarena B.; Gembus, Kelly; Fonseka, Pamali; Sandow, Jarrod J.; Nguyen, Thuy Tien; Tran, Diana; Webb, Andrew I.; Mathivanan, Suresh; Robker, Rebecca L.; Kumar, Sharad
Abstract: Extracellular vesicles (EVs) are important players in cell to cell communication in reproductive systems. Notably, EVs have been found and characterized in the male reproductive tract, however, direct functional evidence for their importance in mediating sperm function is lacking. We have previously demonstrated that Arrdc4, a member of the α‐arrestin protein family, is involved in extracellular vesicle biogenesis and release. Here we show that Arrdc4‐mediated extracellular vesicle biogenesis is required for proper sperm function. Sperm from Arrdc4 –/– mice develop normally through the testis but fail to acquire adequate motility and fertilization capabilities through the epididymis, as observed by reduced motility, premature acrosome reaction, reduction in zona pellucida binding and two‐cell embryo production. We found a significant reduction in extracellular vesicle production by Arrdc4 –/‐ epididymal epithelial cells, and further, supplementation of Arrdc4 –/– sperm with additional vesicles dampened the acrosome reaction defect and restored zona pellucida binding. These results indicate that Arrdc4 is important for proper sperm maturation through the control of extracellular vesicle biogenesis.